2018
DOI: 10.3390/rs10040614
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Concentrated Flowpaths in Riparian Forest Buffer Contributing Areas Using LiDAR Imagery and Topographic Metrics

Abstract: Riparian forest (CP22) buffers are implemented in the Chesapeake Bay Watershed to trap pollutants in surface runoff thus minimizing the amount of pollutants entering the stream network. For these buffers to function effectively, overland flow must enter the riparian zones as dispersed sheet flow to facilitate slowing, filtering, and infiltrating of surface runoff. The occurrence of concentrated flowpaths, however, is prevalent across the watershed. Concentrated flowpaths limit buffer filtration capacity by cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Along the stream networks, the delineation of DRIP/non-DRIP areas in the RZ can help to implement hydrologically adapted buffers in forest management, thereby ensuring that water bodies maintain a good water quality (Kuglerová et al, 2014b;Tiwari et al, 2016;Wallace et al, 2018). Traditionally, forest practices considered fixed width buffers, even though the riparian function is not homogeneous around all water bodies (Buttle, 2002).…”
Section: Docmentioning
confidence: 99%
See 1 more Smart Citation
“…Along the stream networks, the delineation of DRIP/non-DRIP areas in the RZ can help to implement hydrologically adapted buffers in forest management, thereby ensuring that water bodies maintain a good water quality (Kuglerová et al, 2014b;Tiwari et al, 2016;Wallace et al, 2018). Traditionally, forest practices considered fixed width buffers, even though the riparian function is not homogeneous around all water bodies (Buttle, 2002).…”
Section: Docmentioning
confidence: 99%
“…For the hydrological characterization of riparian inputs, various approaches can be used across scales. Although subsurface pathways do not entirely follow surface topography (Devito et al, 2005), it has been demonstrated that topographic depressions are a good indicator of accumulation areas of water, ponding, shallow groundwater tables, and concentrated flow paths in the near-stream area (Ågren et al, 2014;Jencso et al, 2009;Wallace et al, 2018). As such, topographic models can predict where along a stream network disproportionally large amounts of groundwater connect with the stream.…”
mentioning
confidence: 99%
“…Along the stream networks, the delineation of DRIP/non-DRIP areas in the riparian zone can help to implement hydrologically adapted buffers in forest management, ensuring that waterbodies remain their water quality (Kuglerová et al, 2014b;Tiwari Wallace et al, 2018). Traditionally, forest practices considered fixed width buffers even though the riparian function is not homogeneous around all water bodies (Buttle, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of saturated areas in the RZ is linked to preferential hydrological pathways that route upland water towards streams. Although subsurface pathways do not entirely follow surface topography (Devito et al, 2005), it has been demonstrated that topographic depressions are a good indicator for accumulation areas of water, ponding, shallow groundwater tables and concentrated flow paths in the near-stream area (Ågren et al, 2014;Jencso et al, 2009;Wallace et al, 2018). As such, topographic models can predict where along a stream network disproportionally large amounts of groundwater connect 35 with the stream (Leach et al, 2017).…”
mentioning
confidence: 99%
“…This tallies with the decrease in chemical fertilizer use intensity and pesticide use intensity, as farmland reduction inevitably lead to a decrease in the application of these substances (Zaragozí et al, 2012), complying with the "one regulatory, two reduction, three basic" policy promoted by the Chinese government. A previous study has analyzed the relationship between the riparian forest buffer zone and pollution mitigation in Chesapeake bay watershed and found that the wide buffer zone could effectively reduce water pollution (Carlington et al, 2018). Other authors have analyzed the relationship between climate, land use change, and water quality in the Pike river watershed and found that land use changes had an impact on water quality (Mehdi et al, 2015).…”
Section: Land Variations Influence Agnps Risksmentioning
confidence: 99%